Enhancement of OGG1 protein AP lyase activity by increase of APEX protein - Saitoh, Takayuki; Shinmura, Kazuya; Yamaguchi, Satoru; Tani, Masachika; Seki, Shuji; Murakami, Hirokazu; Nojima, Yoshihisa; Yokota, Jun (Mutation Research/DNA Repair, 2001)
8-Hydroxyguanine (oh8G) is a major form of oxidative DNA damage produced by reactive oxygen species (ROS). The human OGG1 gene encodes a DNA glycosylase that excises oh8G from double-stranded DNA. In this study, we investigated a mode of interaction between OGG1 and APEX proteins in the repair of oh8G under oxidative stresses. DNA cleavage assay using oh8G-containing oligonucleotides showed that the phosphodiester bond on the 3′-side of oh8G was cleaved by the AP lyase activity of GST-OGG1 protein and the phosphodiester bond on the 5′-side of oh8G was cleaved by the DNA 3′-repair diesterase activity of APEX protein. Gel mobility shift assay showed that the complex of GST-OGG1 protein and oh8G-containing oligonucleotides mostly changed into the complex of APEX protein and oligonucleotides by addition of APEX protein into the reaction mixture. We next analyzed alterations in the amount of 8-hydroxydeoxyguanosine (oh8dG) in DNA and the levels of OGG1 and APEX expression in HeLa S3 cells treated with 2mM hypochlorous acid, a kind of ROS. An approximately four-fold increase in the amount of oh8G was detected by the HPLC–ECD method. Reverse transcriptase–polymerase chain reaction (RT–PCR) and Western blot analyses indicated that the level of APEX expression increased approximately four-fold, whereas the level of OGG1 expression was unchanged. However, in the DNA cleavage assay, the AP lyase activity of GST-OGG1 protein was significantly increased in the presence of a molar excess of APEX protein. These results indicate that, under severe oxidative stresses, OGG1 mRNA is not induced and the amount of OGG1 protein is not remarkably increased, but the activity of OGG1 protein is enhanced by the increase of APEX protein in the cells.